Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20205025
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Neurotensin in Murine Model of Hapten-Induced Asthma

Abstract: Neurotensin (NT) demonstrates ambiguous activity on inflammatory processes. The present study was undertaken to test the potential anti-inflammatory activity of NT in a murine model of non-atopic asthma and to establish the contribution of NTR1 receptors. Asthma was induced in BALB/c mice by skin sensitization with dinitrofluorobenzene followed by intratracheal hapten provocation. The mice were treated intraperitoneally with NT, SR 142948 (NTR1 receptor antagonist) + NT or NaCl. Twenty-four hours after the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…On the other hand, NT-treated animals in the model of inflammatory bowel disease showed a protective effect on the intestines related to anti-inflammatory, antioxidant, and anti-apoptotic actions [16]. The latest study showed that NT is a potent downregulator of inflammatory and hyperreactivity response in the nonallergic asthma model [17]. We should keep in mind that the activity exerted by the chimeric peptide PK20, used in our study, cannot be considered as a simple conjunction of activities appropriate to its parent peptides or, more precisely, pharmacophores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, NT-treated animals in the model of inflammatory bowel disease showed a protective effect on the intestines related to anti-inflammatory, antioxidant, and anti-apoptotic actions [16]. The latest study showed that NT is a potent downregulator of inflammatory and hyperreactivity response in the nonallergic asthma model [17]. We should keep in mind that the activity exerted by the chimeric peptide PK20, used in our study, cannot be considered as a simple conjunction of activities appropriate to its parent peptides or, more precisely, pharmacophores.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of PK20 (10 mg/kg i.p.) was selected on the basis of an analgesic study performed by Kleczkowska et al [13] and our neurotensin-based study [17]. PK20 applied via IP route of injection was previously shown to be safe, without visible adverse side effects [78].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mouse model of non-atopic asthma characterized by neutrophilia previously described [ 86 , 87 ], with slight modifications, was utilized. Briefly, 50 male mice aged 7–8 weeks, weighing 25–30 g were used in the study, and were randomly divided into 6 groups.…”
Section: Methodsmentioning
confidence: 99%
“…Haptens are also broadly used in rodent models to investigate exacerbation in airway inflammation. Studies with toluene diisocyanate (TDI), trimellitic anhydride (TMA), dinitrofluorobenzene (DNFB), and picryl chloride (PCL), allowed dissecting the hapten-induced allergy as well as the similarities and differences between the different compounds (44)(45)(46)(47). Rodent models of DNFB, a powerful sensitizer of non-atopic asthma (47), have recently shown increased numbers of macrophages in bronchoalveolar lavage fluid (BALF), tracheal hyper-reactivity and a strong neutrophilic-based lung inflammation that could reflect characteristic features of non-atopic asthma in humans (46,48).…”
Section: Eliciting Allergic Airway Inflammationmentioning
confidence: 99%